Studies on Sedum taxa found in Sicily (Italy) for Mediterranean extensive green roofs - Tuttolomondo, Teresa; Fascella, Giancarlo; Licata, Mario; Schicchi, Rosario; Gennaro, Maria Cristina; Bella, Salvatore La; Leto, Claudio; Aprile, Simona (Italian Journal of Agronomy, 2018)
One type of green roof whose function is ecological and environmental rather than aesthetic is the extensive green roof. Many studies have shown that Sedum performs very well compared to other hardy species in substrates of less than 10 cm. It seems that Sedum species are able to survive in very thin substrates; they tolerate extreme temperatures and sudden variations in temperatures, high levels of solar radiation, strong winds, poor substrate fertility and extreme drought. In particular, this paper looks at the potential of a number of species from the Sicilian taxa of the genus Sedum (Crassulaceae), which are considered to be those xerophytes most suited for use in extensive green roof systems for Mediterranean areas. Each taxon was subject to in situ and ex situ observations to gain phenological and ecological data, information on its vegetative propagation capacity and its plant ground cover capacity. The results of this study have led to greater understanding of Sicilian pluriennal Sedum genus entities of potential use in green roof systems in the Mediterranean. The taxa respond particularly well to agamic propagation, showing characteristics suited to nursery production of green roof systems, with the exception of S. amplexicaule subsp. tenuifolium. Growth indices and plant development (ground cover) demonstrated the capacity of a number of Sedum taxa to form a uniform green mantle over time. S. sediforme and S. album subsp. album. showed interesting results, for because of their ability to colonize the substrate, and they could be fundamental in determining the plant structure of the green systems. However, there are also other plants, such as S. amplexicaule var. tenuifolium, and, to a lesser extent, S. dasyphyllum var. dasyphyllum and S. ochroleucum, which are able to contribute to floral diversification and lead to greater biodiversity in the system. These taxa could be used when creating associations of Sedum at lower percentages compared to the structuring species (≤20%).